Orientation of sasi Cultural Values in Maluku - Matitaputty Jenny Koce (EDP Sciences, 2021)
More than the cultural values contained in the management of natural resources in Maluku will always include the principles and traditions of sasi and adat because they are an intrinsic part of a culture which for centuries has proven to be adaptive and resistant to external disturbances. The purpose of this study was to determine the orientation of the cultural value of sasi in Maluku. The method used is qualitative research, where observation, interviews and documentation are used to collect data from informants. The results showed that talking about cultural values in sasi would be related to the concept of the nature of human life, the work of human life, human position and space and time, the nature of man and nature as well as the relationship between humans and humans and other people. Where the culture of sasi illustrates what humans must do, It is hoped that sasi culture will remain a part of the Saparua indigenous people so that people will continue to choose the values of sasi cultural orientation so that social life and ecological life will continue to be sustainable from the control of sasi cultural values.